Cohesive Devices Used in Argumentative Essays of Undergraduate EFL Students in Indonesia - Warna, Dewi; Wijaya, Beni; Sartika, Eka; Riznanda, Winny Agustia (Institut Agama Islam Negeri (IAIN) Curup, 2019)
ABSTRACTThis study analyzed qualitatively the cohesive devices used in argumentative essays of undergraduate EFL students in South Sumatera, Indonesia. Eighty essays were collected from eight universities in which ten essays were obtained from each. Halliday and Hasan (1976) concept of grammatical cohesion was used as the framework for the analysis of the essays. All the cohesive devices were found. Reference had the highest frequency which is 50.24% of the total cohesive devices followed by conjuction which is 37.34%, lexical cohesion which is 7.7% and ellipsis which is 3.57%. Substitution was the least used type of cohesive device which is only 1.15%. In terms of correctness of using the devices, most of the devices were all used properly. It was revealed that there was still few mistakes of using reference and substitution since they both were frequently used in the essays. Hence, it can be concluded that the students are more familiar with the use of reference and conjunction even though they are able to use the other devices as well. Keywords: cohesive devices, argumentative essay